O towarzyszeniu dziecku w rozwoju – zarys koncepcji wychowania w żłobku - Lucyna Telka (Problemy Wczesnej Edukacji)
The article addresses the issue of the tutor’s workshop, the concept of upbringing, possible to be used by tutors in a crèche. An example is the concept of accompanying in development in social pedagogy, emphasizing the non-directive features of the relationship between an adult and a child. The concept of upbringing orients the tutor’s beliefs on the relationship with the pupil by taking up intellectual activity conducive to the exploration, application, and maintaining the requirements of the concept.